1999
DOI: 10.1523/jneurosci.19-06-02368.1999
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Inhibition and Excitation of Phrenic Motoneurons during Inspiration: Phase-Specific Control of Excitability

Abstract: The movements that define behavior are controlled by motoneuron output, which depends on the excitability of motoneurons and the synaptic inputs they receive. Modulation of motoneuron excitability takes place over many time scales. To determine whether motoneuron excitability is specifically modulated during the active versus the quiescent phase of rhythmic behavior, we compared the input-output properties of phrenic motoneurons (PMNs) during inspiratory and expiratory phases of respiration. In neonatal rat br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 70 publications
(96 reference statements)
1
60
1
Order By: Relevance
“…Opiate-mediated disinhibition exists in the hippocampus as discussed above (Bramham and Sarvey, 1996;Jin and Chavkin, 1999;Akaishi et al, 2000) and has been also observed in other brain areas, such as the periaqueductal gray (Vaughan et al, 1997) and the rostral ventrolateral medulla (Hayar and Guyenet, 1998). GABAergic input to phrenic motor neurons during inspiration has been demonstrated by Parkis et al (1999). GABAergic terminals have also been identified by light microscopy near phrenic motor neurons (Zhan et al, 1989).…”
Section: What Is the Role Of Enkephalin In I-aug Cells?mentioning
confidence: 81%
“…Opiate-mediated disinhibition exists in the hippocampus as discussed above (Bramham and Sarvey, 1996;Jin and Chavkin, 1999;Akaishi et al, 2000) and has been also observed in other brain areas, such as the periaqueductal gray (Vaughan et al, 1997) and the rostral ventrolateral medulla (Hayar and Guyenet, 1998). GABAergic input to phrenic motor neurons during inspiration has been demonstrated by Parkis et al (1999). GABAergic terminals have also been identified by light microscopy near phrenic motor neurons (Zhan et al, 1989).…”
Section: What Is the Role Of Enkephalin In I-aug Cells?mentioning
confidence: 81%
“…42,[64][65][66][67][68][69][70][71][72] For example, local blockade of GABA synthesis (by application of anti-glutamate decarboxylase 65/67 siRNA) in the vicinity of the phrenic nucleus leads to increasing tonic and phasic activity in PhN discharge on the side of treatment. 71 It has been shown that tonic inhibition in spinal ventral horn interneurons is mediated by α5 subunit-containing GABA A receptors.…”
Section: Candidate Neuroanatomical Substrates For Generation Of Phasimentioning
confidence: 99%
“…Inhibitory synaptic control of excitability during the active phase will affect the timing of burst onset and offset (affecting onset of muscle contraction and relaxation), firing pattern, and recruitment order (961,969,1049,1377,1379). Inhibitory inputs during the quiescent phase in a motoneuron, e.g., during the expiratory phase in an inspiratory neuron, will reduce the probability of spurious, and inappropriate, activation (1049).…”
Section: C) Presynaptic Actions Of Gaba a Receptorsmentioning
confidence: 99%
“…Inhibition may also provide phase-specific control of motoneuron gain, as suggested by the observation of a phasic inspiratory inhibition of phrenic motoneurons that matches the shape and time course of their inspiratory excitatory drive (961). Because phrenic motoneurons (444), like most motoneurons (292,1084,1143,1221,1394), participate in multiple behaviors, such a mechanism may contribute to the optimization of motoneuron excitability for different motor tasks.…”
Section: C) Presynaptic Actions Of Gaba a Receptorsmentioning
confidence: 99%